Leveraging the Aspects of Knowledge, Attitude, and Practice as an Alternative to Prevent Detrimental Impacts of Stunting - Novia Luthviatin; Ninna Rohmawati; Dwi Martiana Wati; Jihan Darmaningtyas; Yessinia Hanatha Pasha (Amerta Nutrition)
Background: The prevalence of stunting in Indonesia is recorded at 21.6% among children under five, while the WHO target for 2025 is less than 14%. Prevention efforts are crucial for mitigating its detrimental impacts. One of the early prevention efforts is health education about nutrition through strengthening knowledge, attitudes, and practices related to healthy food consumption.